Morphology: New Words Phenomenon Existed in Indonesian Language in Youth Communication - Moh. Shofi Zuhri (Institut Agama Islam Tarbiyatut Tholabah, 2023)
In morphology, the formation of new words is based on the word-formation process. The word-formation process itself is the concept of how new words can be formed. Several processes underlie the formation of new words in a language. This theory is based on Yule (2010). A comprehensive analysis requires answers to questions. 1. How new words are formed in Indonesian language communication, 2. What formations are dominant in the formation of new words? Observation serves as a data collection tool. The author collects new words to determine the natural word formation conditions used in communication and to identify the process of word formation without the intervention of the researcher. Finally, they are classified according to the process of word formation. This study uses data triangulation to ensure the research obtains valid data. The first-word formation process is blending which dominates the formation of new words in Indonesian with 13 processes found. The second process that dominates is the acronym with 8 found processes. The clipping process also includes the most processes in the formation of new words with 5 processes. The creation of new words found is not only blending, acronyms and clipping but also borrowing processes with 3 processes and compounding with 1 process. The first-word formation process is blending which dominates the formation of new words in Indonesian with 13 processes found. The second process that dominates is the acronym with 8 found processes. The clipping process also includes the most processes in the formation of new words with 5 processes. The creation of new words found is not only blending, acronyms and clipping but also borrowing process with 3 processes and compounding with 1 process.